The development of accurate force fields for protein simulation - Jiao, Yuanfang (Kansas State University, 2012)
Computer simulations have provided a wealth of information concerning a wide range of systems. The precision of computer simulation results depends on the degree of sampling (time scales) achieved, while the accuracy of the results (given sufficient sampling) depends on the quality of force field used. A force field provides a description of the energy for a system of interest. Recently, we have been developing a Kirkwood Buff (KB) force field for molecular dynamics simulations of biological systems. This force field is based on the KB Theory of solutions, emphasizing the accurate description of intermolecular interactions, and reasonably reproducing a range of other physical properties from experiment. In this approach simulation results in terms of KB integrals can be directly compared with experimental data through a KB analysis of the solution properties. The approach therefore provides a simple and clear method to test the capability of a force field. Here we firstly studied a series of alcohol-water mixtures in an attempt to validate the transferability and additivity of the force field. A general fluctuation theory was applied to investigate the properties of these systems, and to compare with computer simulation results. The possible effects of cosolvents on peptides and proteins were then investigated using N-methylacetamide as model for the peptide backbone and urea as cosolvent. A possible explanation for the urea denaturation of protein structure was provided using a thermodynamics point of view involving transfer free energies and preferential interactions obtained from the KB integrals. Finally, potentials for protein backbone and sidechain torsions were developed by fitting to quantum mechanical calculations and NMR data. Simulations of a variety of peptides and proteins in aqueous solutions were then performed to demonstrate the overall reliability of the force field.
Keywords: Protein simulation; Force field; Chemistry (0485)